A 3D collision avoidance strategy for UAV with physical constraints. (January 2016) - Zhu, Lihua; Cheng, Xianghong; Yuan, Fuh-Gwo
Highlights: The potential problems of the APF method have been analyzed in UAV application. A modified APF method is used to implement the UAV collision avoidance path planning. The uncertain zone of obstacles increases the safety of the UAV path planning. A proposed frame decouples the decomposed forces on UAV with physical constraints. The incorporation of the UAV physical constraints ensures a reachable path for UAV. Abstract: The main goal of this research effort is to find a flyable collision-free path for an unmanned aerial vehicle (UAV) in a dynamic environment. Given that the UAV path planning needs to adapt in near real-time to the dynamic nature of the operational scenario, and to react rapidly to updates in the situational awareness, a modified artificial potential field (MAPF) approach is utilized to provide collision avoidance in view of pop-up threats and a random set of moving obstacles. To ensure a practically reachable trajectory, this paper proposes a constraint reference frame to develop MAPF so that the decomposed forces from MAPF can be matched with the physical constraints of the UAV for online adjustment. Simulations and experimental results provide promising validation in terms of the efficiency and scalability of the proposed approach.